2006
DOI: 10.1079/bjn20061764
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of vitamin B6 delays homocysteine-induced atherosclerosis in rats

Abstract: Elevated plasma homocysteine is a risk factor for atherosclerotic disease. In the present study, we have examined whether the oxidative stress due to a low level of vitamin B 6 accelerates the development of homocysteine-induced atherosclerosis in rats. First, the effect of homocysteine thiolactone intake (50 mg/kg per d) on vascular integrity, lipid peroxide concentration, endothelial NO synthase (eNOS) expression and biochemical profiles was examined at day 1, day 21 and day 42 (five rats per group). The his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 39 publications
(29 reference statements)
2
29
0
1
Order By: Relevance
“…Considering the epidemiological evidence of a role of vitamin B 6 in inflammatory-related diseases and the observed relationship with inflammatory markers (11,16,18,79) , it is plausible that vitamin B 6 plays a role in CVD pathogenesis through mechanisms linked to inflammation (Table 4). Therefore, with the knowledge that systemic acute-phase markers are solid and independent risk factors for CAD (80,81) , that inflammation exerts an essential role in all stages of the atherosclerotic process (82) and the possibility that vitamin B 6 has a role in inflammatory processes, several mechanisms were proposed linking low vitamin B 6 and CVD using cell culture studies, animal studies (72) and clinical trials. Animal studies have reported that inflammation reduces circulating and hepatic concentrations of vitamin B 6 .…”
Section: Yesmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the epidemiological evidence of a role of vitamin B 6 in inflammatory-related diseases and the observed relationship with inflammatory markers (11,16,18,79) , it is plausible that vitamin B 6 plays a role in CVD pathogenesis through mechanisms linked to inflammation (Table 4). Therefore, with the knowledge that systemic acute-phase markers are solid and independent risk factors for CAD (80,81) , that inflammation exerts an essential role in all stages of the atherosclerotic process (82) and the possibility that vitamin B 6 has a role in inflammatory processes, several mechanisms were proposed linking low vitamin B 6 and CVD using cell culture studies, animal studies (72) and clinical trials. Animal studies have reported that inflammation reduces circulating and hepatic concentrations of vitamin B 6 .…”
Section: Yesmentioning
confidence: 99%
“…Inflammation and vitamin B 6 -related atherogenesis PLP functions as a coenzyme in more than 100 reactions that are involved in the metabolic pathways of neurotransmitters as well as in the metabolism of amino acids, lipids and carbohydrates (72) . PLP also takes part in other significant pathways related to immune function (73) , thrombosis (74,75) and inflammation (17) , all of which are crucial mechanisms in every stage of the atherosclerotic process.…”
Section: Yesmentioning
confidence: 99%
“…Further, immuno-histochemical studies with ApoE -/-mice show that N-Hcy-protein accumulates in aortic lesions and is enhanced in animals fed a HHcy diet [21]. Treatments with Hcy-thiolactone produce atherosclerotic changes in baboons [22] and rats [23], and cause developmental abnormalities in eyes of chick embryos, including optic lens dislocation, ectopia lentis [24], a diagnostic feature prevalent in CBS-deficient patients [3].…”
mentioning
confidence: 99%
“…Deficiency in vitamin B6 is associated with increased homocysteine level and oxidative stress potentially involved in accelerated atherosclerosis (Endo et al, 2006). During Amadori reactions, these highly reactive intermediate carbonyl groups, known as a-dicarbonyls or a-oxoaldehydes that generated from carbonyl stress, are important in the course of all stages and pathways of glycation.…”
Section: Discussionmentioning
confidence: 99%